A Potential Effect of Cordycepin on the Feedback between Polyadenylation and PI3K/Akt/mTOR Signalling - Lawrence, Steven (2023)
Polyadenylation is a key step in mRNA maturation and leads to the sequential addition of adenosines forming a poly(A) tail, which is important in mRNA stability, nuclear export, transcription termination, and translational control. This process requires RNA-binding proteins, such as polyadenylation machinery, in pre-mRNA 3’processing multiprotein complexes. Cordycepin (3’-deoxyadenosine) is a natural compound known to metabolise to cordycepin triphosphate (CoTP), which once incorporated into the poly(A) tail, causes chain termination and is thought to restrict the dissociation of polyadenylation machinery such as WDR33. There are known effects of cordycepin on inflammation, cancer progression, and signal transduction pathways, such as PI3K/Akt/mTOR signalling, however the clear mechanism of action of cordycepin is still elusive.